Женщины, кот и собака: [сборник] / Мария Метлицкая - Метлицкая Мария (За чужими окнами, 2016)
Экземпляры: (20170929) / Инвентарный номер: 39398 / Цена: 72.70 / Сис.шифр: Р2 / Авт.знак: М 54 / ГРНТИ: 17.82.82 / ББК: 84(2Рос=Рус)